Market opportunity development process: Multiple case study on Finnish SMEs internationalizing to emerging markets - Maijala, Lotta (My University, 2016)
The main objective of the thesis was to examine how international market opportunities develop in small and medium-sized enterprises (SMEs). The opportunity development of SMEs in international context has not been the focus of many in-depth qualitative studies. The theoretical part of the research focused on international entrepreneurship, opportunity formation, foreign market knowledge and network view. The preliminary theoretical framework is built on the concepts of market orientation, international exposure, network-embedded foreign market knowledge, entrepreneurial alertness and market knowledge competence. The theoretical framework also included the core process of opportunity development, which is defined by perception, discovery and creation of opportunities. The framework was empirically tested with a multiple case study. The empirical part was based on face-to-face interviews with Finnish SMEs developing market opportunities to emerging markets. The empirical analysis supports the theoretical findings to a large extent. It can be concluded that entrepreneurs’ and the SMEs’ previous international experience had an impact on the opportunity development by increasing the alertness and foreign knowledge competence of the firms. In addition, empirical results support the theoretical finding that internationalizing SMEs develop their foreign market knowledge principally in networks. Furthermore, foreign information received from institutional, business and social networks worked often as an initiative for the SMEs to launch their opportunity development. Proactiveness and curiosity towards all information in networks are central for SMEs’ market orientation. Market orientation developed towards market knowledge competence by processing the market information within their organizations. For this, inter-functional knowledge sharing and constant innovation were essential. The core process of opportunity development was dynamic and iterative. It included phases of both creation and discovery, although often shifting towards creation as the firm’s market presence stabilized.
Keywords: Market opportunity; market orientation; foreign market knowledge; networks; internationalization; emerging markets; small and medium-sized enterprises; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|